Parallel progressive precomputed radiance transfer - Santos, Luís Paulo (2006)
Precomputed Radiance Transport (PRT) was introduced as a technique to enable interactive navigation and distant environmental real time relighting of rigid scenes. Evaluating radiance transport is, however, a computationally very demanding task, which precludes PRT's utilization during the model design phase, since the user must wait for long periods of time before being able to light and navigate within the model. This paper proposes and validates an approach to provide visual feedback to the user as soon as possible, within PRT context. By resorting to parallel processing and progressive refinement, the user is quickly presented with a lower lighting resolution of the virtual model. This is then progressively refined by incrementally increasing the number of incident directions taken into account on transport computations. PRT is, however, a complex algorithm that requires frequent collective communications of huge volumes of data, thus constraining the maximum achievable speedup on a parallel system. This issue is analysed and an alternative workload distribution is proposed and evaluated on a 12 node dual processor cluster. The final solution ensures a good resource utilization rate, reducing response times from dozens of seconds to a few hundred milliseconds.